Weekly versus Daily Iron Supplementation for Preventing Iron deficiency Anaemia Amongst Children Between Six to 24 Months: A Randomised Control Trial - Kaushik, Sneha; Yadav, Anita; Debata, Pradeep Kumar; Aggarwal, Kailash Chandra (Journal of Nepal Paediatric Society, 2019)
Introduction: Iron deficiency anaemia is common in developing nations and starting iron supplementation from infancy is an important measure for its prevention. There is still not enough evidence, whether giving iron twice weekly as compared to daily, is enough to prevent the same. Methods: This open-labeled randomised control trial was conducted at a tertiary care facility over a period of 1.5 years. After informed consent from parents, a total of 125 non-anaemic healthy infants in age group six to 24 months; with birth weight > 2500 grams, born singleton at term gestation and predominantly breastfed in the first six months of life; were randomised using computer generated sequence to two groups. Control group received daily elemental iron supplementation of 1 mg/kg/day and the intervention group received twice weekly 2 mg/kg/day. Haemoglobin, serum ferritin were measured at enrolment and at the end of 100 days. Primary outcome was anaemia defined as haemoglobin less than 11 mg/dl. Secondary outcome measures were weight gain, increase in length and occipito-frontal circumference. Results: Baseline characteristics were similar in the two groups. This study showed significantly higher mean haemoglobin (mg/dl) (mean ± SD 11.882 ± 0.3237, 11.683 ± 0.4264, p = 0.009) and mean serum ferritin (ng/ml) (mean ± SD 101.704 ± 23.0263, 62.149 ± 24.2079, p = 0.000) at end of 100 days in the control group than the intervention group. There was no difference in any of the secondary outcomes. Conclusions: Biweekly iron supplementation can also prevent iron deficiency anaemia in children between six to 24 months of age but daily is better in respect to the increase in haemoglobin.